Pengaruh Karakteristik Komite Audit dan Audit Tenure terhadap Financial Restatement - Jessica Octavia; Sany Sany (Business Accounting Review, 2021)
This study aims to investigate the impact of audit committee characteristics (audit committee size, audit committee independence, and audit committee expertise) and audit tenure on the likelihood of financial restatements. The independent variables in this study are audit committee size (ACS) and audit tenure (AT) that were measured nominally, audit committee independence (ACI), and audit committee expertise (ACE) measured by ratio scale. The dependent variable in this study is financial restatement (FR) that measured by a dummy variable. The samples used were selected by the purposive sampling method. The samples were 70 financial companies that were listed on the Indonesia Stock Exchange (IDX) for 5years period (2016-2020). The data were collected from financial reports, annual reports, and Bloomberg. The analysis technique used was logistic regression analysis. The test showed that audit committee size and audit committee independence have no significant effect on the likelihood of financial restatement while the audit committee expertise andaudit tenure have a significant effect on the likelihood of financial restatement.